SOSIALISASI PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA DALAM MENDUKUNG PROGRAM BUMDES SIMA SARI DANA DI DENPASAR - Ida Ayu Putu Widani Sugianingrat; Putu Herny Susanti; Ni Wayan Alit Erlina Wati; I Wayan Budi Satriya; I Wayan Arik Suwitra; I Komang Alit Anggara Wijaya Kusuma; Ni Luh Putu Agustiari Sisca Dewi (UNHI Press, 2022)
Household waste is one of the largest contributors of waste to the environment. We can start with waste management on a household scale by separating organic and inorganic waste. Efforts are made to reduce pollution and reduce the volume of waste piles, it is necessary to manage waste, especially organic waste generated from community activities and reused as fertilizer. BUMDes Sima Sari Dana has a waste management business unit, by carrying out business activities for collecting and transporting waste from the residents of Kesiman Petilan village; Garbage bank; Production of compost, and coal fossil fuel reduction pellets. Based on interviews that have been conducted with the BUMDes manager Sima Sari Dana, it is known that the problem faced is the lack of awareness of the people of Kesiman Petilan village in sorting organic and inorganic waste in their respective households, this condition causes delays in the composting process, due to inefficiency. time and costs faced by BUMDes. This condition also causes the potential for marketing and processing of fertilizers from the generated waste to be less than optimal. The stages carried out in this community service activity are to set targets for which socialization will be given about the importance of sorting organic and non-organic waste and how to process organic waste into compost at BUMDes Sima Sari Dana Kesiman Petilan, determine the form and media of socialization used , taking into account the cost aspect, and the latest trends in community communication, it was decided that the socialization would be carried out by making educational videos or socializing the importance of sorting waste and the process of making compost at BUMDes Sima Sari Dana Kesiman Petilan. The educational and socialization videos are packaged in a comedy genre, with an emphasis on knowledge about the types of organic and inorganic waste and the process of making compost. Furthermore, the video will be submitted to the Kesiman Petilan Village Government to be then forwarded to each Hamlet Head which is then forwarded to all residents in the area through communication media such as WhatsApp, Telegram or Facebook. Not only that, this educational and outreach video was also uploaded to YouTube as an effort to disseminate information to the public other than the people of Kesiman Petilan Village.